2006
DOI: 10.1243/095441105x69132
|View full text |Cite
|
Sign up to set email alerts
|

Development rationale for an articular surface replacement: A science-based evolution

Abstract: Hip resurfacing has an enduring appeal because of the advantages of bone conservation and maximal joint stability. However, a far from satisfactory experience with earlier resurfacing designs led to its virtual disappearance in the 1980s. The concept was reintroduced in the late 1990s. The current generation of resurfacing devices generally consisted of a large-diameter metal-on-metal articulation, the femoral components being cemented and the acetabular components utilizing various forms of cementless fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 53 publications
3
19
0
Order By: Relevance
“…Another important factor to consider is the effect of the tribochemical layer which involves the incorporation of proteins into a nanocrystalline surface layer which can regenerate and repair itself inducing low wear rates. 27 Initially, there was an apparent difference in the steady state wear rates (1)(2)(3)(4)(5) between the two bearing sizes. However, in late steady state (10)(11)(12)(13)(14)(15) Mc) the wear rates were similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another important factor to consider is the effect of the tribochemical layer which involves the incorporation of proteins into a nanocrystalline surface layer which can regenerate and repair itself inducing low wear rates. 27 Initially, there was an apparent difference in the steady state wear rates (1)(2)(3)(4)(5) between the two bearing sizes. However, in late steady state (10)(11)(12)(13)(14)(15) Mc) the wear rates were similar.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages and disadvantages of surface replacement arthroplasty have been discussed previously. [1][2][3] Bearing diameter, clearance and the resultant effective radius (R) are key parameters in the tribology of MoM hip replacements. Previous simulator studies on MoM total hip replacements have demonstrated a 2-3-fold reduction in wear with increasing head size.…”
Section: Introductionmentioning
confidence: 99%
“…A hip simulator study represents a complex undertaking while still representing an over-simplification of patient conditions. A major body of work over the years identified fluid-film lubrication as the ideal condition for success in MOM bearings [12,13,16]. However, MOM bearings failing in patients have demonstrated adverse wear mechanisms that can produce significantly high volumes of CoCr debris within a few years [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In hip simulator laboratories, a major body of research identified fluid-film lubrication as one of the goals for achieving success with hip bearings [12][13][14][15][16][17][18]. Large MOM bearings appeared particularly suited to this concept.…”
Section: Introductionmentioning
confidence: 99%
“…Hip resurfacing is a type of hip arthroplasty that is commonly compared to total hip replacement. Total hip replacements involve resecting the femoral neck and placing a long stemmed femoral component into the proximal shaft of the femur (Isaac, Siebel et al 2006). The two types of arthroplasty seen in figure 1 show the fundamental differences between the two systems.…”
Section: Introduction the Development Of Hip Resurfacingmentioning
confidence: 99%